2017
DOI: 10.1002/ange.201704513
|View full text |Cite
|
Sign up to set email alerts
|

Visible‐Light‐Driven Palladium‐Catalyzed Radical Alkylation of C−H Bonds with Unactivated Alkyl Bromides

Abstract: Reported herein is an ovel visible-light photoredox system with Pd(PPh 3 ) 4 as the sole catalyst for the realization of the first direct cross-coupling of C(sp 3 )ÀHb onds in N-aryl tetrahydroisoquinolines with unactivated alkyl bromides. Moreover,i ntra-and intermolecular alkylations of heteroarenes were also developed under mild reaction conditions.A variety of tertiary,s econdary,a nd primary alkylb romides undergo reaction to generate C(sp 3 )ÀC(sp 3 )and C(sp 2 )ÀC(sp 3 ) bonds in moderate to excellent y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(8 citation statements)
references
References 85 publications
1
7
0
Order By: Relevance
“…[33][34][35] Additionally, X-ray photoelectron spectroscopy (XPS) measurements were performed and indicate the presence of three distinct Pd oxidation states, namely Pd(0), Pd(I) and Pd(II), which suggests that Pd(I) species may be involved in the process. Based on these preliminary mechanistic studies and supported by recent reports by Gervogyan, [42][43][44][45][46][47][48] Shang and Fu, 34,49,50 Yu, 51 and Rueping 52 , we proposed that a hybrid alkyl Pd(I) radical species VII is generated from the NHP ester 1a by SET from the photoexcited palladium catalyst. [33][34][35] Recent developments in alkyl Heck-type reactions have shown that the hybrid alkyl Pd(I) radical species could be generated by visible light and can subsequently react efficiently with styrene-type substrates.…”
Section: Modification Of Complex Architecturessupporting
confidence: 71%
“…[33][34][35] Additionally, X-ray photoelectron spectroscopy (XPS) measurements were performed and indicate the presence of three distinct Pd oxidation states, namely Pd(0), Pd(I) and Pd(II), which suggests that Pd(I) species may be involved in the process. Based on these preliminary mechanistic studies and supported by recent reports by Gervogyan, [42][43][44][45][46][47][48] Shang and Fu, 34,49,50 Yu, 51 and Rueping 52 , we proposed that a hybrid alkyl Pd(I) radical species VII is generated from the NHP ester 1a by SET from the photoexcited palladium catalyst. [33][34][35] Recent developments in alkyl Heck-type reactions have shown that the hybrid alkyl Pd(I) radical species could be generated by visible light and can subsequently react efficiently with styrene-type substrates.…”
Section: Modification Of Complex Architecturessupporting
confidence: 71%
“…The C(sp 2 )–H alkylation of arenes with an alkyl electrophile could be an ideal synthetic method for the construction of alkylarenes, as it would avoid the regioselectivity issues associated with the olefin hydroarylation reactions. However, despite significant advances in the field of C–H alkylation, the majority of the reported transition metal-catalyzed C(sp 2 )–H alkylation reactions using alkyl electrophiles require directing groups 13 , 14 , or have a limited applicability to heteroarenes 15 18 , activated electron-deficient arenes 19 , and intramolecular alkylation systems 16 , 20 , 21 . This significantly limited scope is due to the challenging oxidative addition to the alkyl electrophile and the high C–H activation barrier of the unactivated arenes (C–H bond dissociation energy, ~110 kcal/mol) 22 .…”
Section: Introductionmentioning
confidence: 99%
“…Although homolytic aromatic substitution (HAS), the radical analog of the electrophilic aromatic substitution, has been well developed 24 , 25 , the insertion of nucleophilic alkyl radicals to the electron-rich π-system of arenes is significantly more sluggish and the alkyl radicals are prone to undergo side reactions, such as homodimerization and hydrogen atom transfer (HAT) 23 , 26 , 27 . To control the reaction pathways, the recently reported photoinduced Pd catalysis approach was identified as an attractive activation mode to generate alkyl radicals from alkyl halides, since it operates under mild conditions while controlling the concentration of free radical species to suppress undesired side reactions 16 , 19 , 28 36 . Applying the photoinduced Pd catalysis, Gevorgyan and co-workers first succeeded in developing the photoinduced Pd-catalyzed Heck reaction of alkyl halides by utilizing Pd(I)/alkyl radical hybrid species generated by single-electron transfer (SET) activation 37 , 38 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2006, Li and coworkers reported a crossdehydrogenative-coupling reaction, which could directly couple the α-C(sp) 3 -H of tertiary amines with nucleophiles under oxidative conditions [46][47][48][49] . Very recently, the photoredox-induced α-C (sp) 3 -H functionalization of tertiary amines was achieved, which could functionalize the α-C(sp) 3 -H under mild and external oxidant-free conditions 50,51 . Despite these achievements, the direct C(sp 3 )-C(sp 3 ) cross-coupling reactions between tertiary amines α-C(sp 3 )-H and unactivated C(sp 3 )-H were still not realized.…”
Section: C(sp 3 )-C(sp 3 ) Cross-couplingmentioning
confidence: 99%